Analisis Efisiensi dan Efektivitas Pengelolaan Dana ZIS pada Laznas Baitulmaal Muamalat - Mualo, Hamidatuzzahra; Rohim, Ade Nur (Islamic Economics and Business Review, 2023)
The management of Zakat, Infak and Alms funds at LAZ in Indonesia has been well implemented because LAZ's performance has also been good, but in some LAZs the management of ZIS funds needs to be considered so that the level of efficiency and effectiveness of management is still not comprehensive. This study aims to analyze the efficiency and effectiveness of the management of zakat, infaq and alms funds at the Baitulmaal Muamalat National Amil Zakat Institute. This study uses a quantitative approach with secondary data sources in the form of financial reports. The analytical method uses Data Envelopment Analysis (DEA) to measure efficiency while the Allocation to Collection Ratio (ACR) analysis method to measure effectiveness. The results of this study indicate that in 2016 and 2017 Laznas Baitulmaal Muamalat was inefficient in managing ZIS funds, while in 2018-2021 it was efficient. To calculate the effectiveness of managing ZIS funds, in 2016 and 2017 they received the title of Effective, while in 2018-2021 they received the title of Highly Effective.